Analisis dan Perancangan Sistem Informasi Manajemen Perpustakaan - Basmallah Ramadhani Aisyah Putri (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The library management information system for SMP Negeri 2 Solear has been successfully implemented. Purpose of creating this information system is to make it easier for members to see the list of available books and borrow books easily, namely online, and to help admin staff in managing book, member and book borrowing data. This information system has two views, namely the user page and the admin page. On the user page, users can register as library members, see available books, and can borrow the books they want. On the admin page, the admin can add, subtract and manage book data, view members' borrowing history, and can see the number of books available. This application was created using PHP and MySQL programming languages, the writing method used was System Development Life Cycle (SDLC), system design used Unified Modeling Language (UML), and system display design used Dia Diagram. It is hoped that with this information system users and admins can access the system anywhere and anytime via the internet. And users don't need to come to the library just to see the availability of the books they want to borrow. Apart from that, admin work can be lighter without taking notes manually.